The Intersection of Laboratory Testing and Physical Therapy: Implications for Patient Rehabilitation – A Systematic Review - Alqahtani, Musab Fahad; Alqahtani , Ali Saad; Asiri, Abdullah Yahya; Alqahtani , Rawan Jarman; Arishi, Abdulhakim Abdullah; Alqahtani, Shuruq Yahya (Journal of Ecohumanism, 2024)
This systematic review explores the intersection of laboratory testing and physical therapy in the context of patient rehabilitation, emphasizing the role of diagnostic markers in optimizing therapeutic outcomes. The integration of laboratory diagnostics into physical therapy practices has gained significant attention, as it enables more personalized and effective rehabilitation strategies. This review synthesizes findings from recent studies, highlighting the influence of laboratory tests, such as blood biomarkers, imaging, and metabolic evaluations, on tailoring therapy plans and enhancing recovery. Results demonstrate the potential of diagnostic data to refine physical therapy interventions, improve patient outcomes, and reduce recovery times. However, challenges such as cost, accessibility, and the need for interdisciplinary collaboration remain critical considerations. The findings underline the importance of leveraging laboratory diagnostics to advance evidence-based physical therapy and promote comprehensive, patient-centered care.